Let's go through the steps to complete the square for the equation \( x^2 + 12x - 14 = 0 \).
-
Start with the original equation: \[ x^2 + 12x - 14 = 0 \]
-
Move the constant term to the other side: \[ x^2 + 12x = 14 \]
-
To complete the square, we take half of the coefficient of \( x \) (which is 12), square it, and add it to both sides. Half of 12 is 6, and squaring it gives us 36: \[ x^2 + 12x + 36 = 14 + 36 \]
-
Now we can rewrite the left side as a squared binomial: \[ (x + 6)^2 = 50 \]
-
Now take the square root of both sides: \[ x + 6 = \pm \sqrt{50} \]
-
This simplifies to: \[ x + 6 = \pm 5\sqrt{2} \]
-
Isolate the variable \( x \): \[ x = -6 \pm 5\sqrt{2} \]
The final answers are:
- \( x = -6 + 5\sqrt{2} \)
- \( x = -6 - 5\sqrt{2} \)
Here are your responses filled in:
- \( x^2 + 12x + 36 \)
- \( 14 + 36 \)
- \( (x + 6)^2 \)
- \( 50 \)
- Take the square root of both sides.
- \( x + 6 = \pm \sqrt{50} \)
- \( x = -6 \pm 5\sqrt{2} \)
Final answers are:
- \( x = -6 + 5\sqrt{2} \) and \( x = -6 - 5\sqrt{2} \)